A Tetrasilicon Analogue of Bicyclo[1.1.0]but‐1(3)‐ene Containing a Si=Si Double Bond with an Inverted Geometry. Issue 13 (21st February 2019) - Iwamoto, Takeaki; Abe, Takashi; Sugimoto, Kunihisa; Hashizume, Daisuke; Matsui, Hiroshi; Kishi, Ryohei; Nakano, Masayoshi; Ishida, Shintaro
Abstract: Bicyclo[1.1.0]tetrasil‐1(3)‐ene 1, a tetrasilicon analogue of bicyclo[1.1.0]but‐1(3)‐ene that contains a formal double bond between bridgehead silicon atoms in an inverted geometry, was synthesized and isolated in the form of thermally stable orange crystals. The distance between the bridgehead Si atoms in 1 is much longer than those in typical Si=Si bonds, but still shorter than that of a previously reported pentasila[1.1.1]propellane. DFT calculations suggest that the bridgehead bond in 1 comprises a σ bond with an inverted geometry and a π bond. This notion is supported by the UV/Vis spectrum of 1, which exhibits several absorption bands in the UV/Vis region. While 1 is stable toward typical trapping agents for Si=Si double bonds, 1 reacts with carbon tetrachloride to furnish a hexachlorotetrasilane. Abstract : Let me Si : A tetrasilicon analogue of bicyclo[1.1.0]but‐1(3)‐ene that contains a formal double bond between bridgehead silicon atoms in an inverted geometry was synthesized and isolated in the form of thermally stable orange crystals. Experimental and theoretical results suggest that the bridgehead Si−Si bond comprises a σ bond with an inverted geometry and a π bond.